HUBUNGAN PARTISIPASI PENYUSUNAN ANGGARAN DENGAN KINERJA PENGELOLAAN KEUANGAN DAERAH: KEPUASAN KERJA DAN MOTIVASI SEBAGAI VARIABEL PEMODERASI - Fariyana Kusumawati; Muhammad Agus Salam (Universitas Trunojoyo Madura, 2012)
This research aims to test and analyze the relationship between participative budgeting and regional financial statement management performance: job satisfaction and motivation as moderating variables in local-government of Sampang district. The population of this research was all of government staffs who manage regional government financial system (i.e., SKPD) in Sampang district totally 27 SKPD. Purposive sampling was used to take the sample with the total of 91 respondents. Primary data was used in study. The first hypothesis was tested using simple linear regression, where the second and third hypothesis were tested using Moderated Regression Analysis (MRA) with residual approach. In this study, contingent variables was used to evaluate the effectiveness of participation in budgeting to regional financial management performance i.e. job satisfaction and motivation. This study found that first hypothesis was supported suggesting that participative budgeting affects regional financial management performance. The more intensive the participation to make a budget, the better performance is the regional financial management. The second and third hypothesis, predicting that job satisfaction and motivation would moderate the relationship between participative budgeting and regional financial management performance were not supported.